Reading the Chinese Soft Power: A Civilizational Perspective (Prithvi Academic Journal, 2026)
The rise of China on the global stage in recent decades has been influential. Beyond its economic and military prowess, China's soft power its ability to influence and shape the global economic and cultural landscape has increased. This power has also been instrumental in implementing Chinese foreign policy. In this context, this research attempted to analyze the projection of the Chinese soft power and the projects to implement it. In the critical lens of soft power theory, the research aimed to provide valuable insights into how China's unique experiences, interactions, and perceptions can provide a more comprehensive understanding of soft power. Methodologically, the study followed a process-tracing research method that offers a rich and detailed way to investigate and explain causal agents, contributing to a deeper understanding of complex phenomena. This study is fundamentally descriptive and analytical. It employs secondary sources such as books, journal articles, internet sources, and newspaper articles as a reference. This study discussed about the history, uses the lens of Confucian ideology, and success stories in economic growth and poverty alleviation. Furthermore, the study examined the major foreign policy departure of China to analyze soft power as a whole.